Overview of Career Maturity in Class XII Students in High School: Gambaran Kematangan Karir Pada Siswa Kelas XII di Sekolah Menengah Atas - Lailatunnikma Lailatunnikma; Dwi Nastiti (Academia Open, 2021)
Career is an important issue in human life which includes the development of a lifelong decision-making process. Career maturity is the readiness of individuals in choosing a career and making career decisions that are in accordance with the will of the heart and personality tendencies and stages of career development. This study aims to determine the career maturity of class XII students. This research uses descriptive quantitative method. The sample used is class XII students who attend SMA Al-Islam Krian Sidoarjo. The number of samples in this study was 221 students. The sampling method used in this research is simple random sampling. The data collection method uses a Likert scale, namely the career maturity scale. The results of the reliability test on the career maturity scale show a reliability coefficient of 0.943. The result of data analysis from this research is that the career maturity of the XII grade students of SMA Al-Islam Krian Sidoarjo is in the medium category. The results of further research that the percentage of high career maturity aspects is the career exploration aspect. The second in terms of type, women are taller than men. The third is in terms of school majors, science majors are higher than social studies and language majors. Keywords: career maturity, students